One programme too many? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
At the end of March 2000 the BBC World Service weekly radio programme 'The Farming World' ended its record-breaking 40-year run. Not that this widely respected programme had run out of steam. No, it simply ran up against the BBC programme planners,...